Mitigation Strategy of Islamic Financing Risk: A Case of Bank Jatim Syariah - Syaifuddin, Syaifuddin; Sanmas, Abu; Hedi Turmudi, Asep (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
This study examines the financing risk management practices of Bank Jatim Syariah, a prominent provincial-owned Islamic bank in Indonesia with total assets of IDR400 trillion, in response to the rising trend of Non-Performing Financing (NPF) in Islamic banking over the past decade. The research focuses on Bank Jatim Syariah due to its extensive service area, large customer base, and substantial financing portfolio. Employing a qualitative methodology, data was collected through interviews with the bank's financing committee and management, coupled with an analysis of pre-pandemic financing documents. The findings reveal that Bank Jatim Syariah has successfully implemented a robust NPF mitigation mechanism, including debt restructuring, debt scheduling, and both litigious and non-litigious dispute resolution strategies. These measures have effectively reduced NPF levels below 2.35%, minimized bank losses, and ensured the bank's continued ability to serve its 40 million customers in East Java. The study highlights the importance of proactive risk management strategies in maintaining the stability and growth of Islamic banking institutions.======================================================================================================== ABSTRAK – Strategi Mitigasi Risiko Pembiayaan pada Bank Jatim Syariah. Penelitian ini mengkaji praktik manajemen risiko pembiayaan Bank Jatim Syariah, salah satu bank syariah terbesar milik pemerintah daerah di Indonesia dengan total aset Rp.400 triliun. Hal ini sebagai respons terhadap tren peningkatan Non-Performing Financing (NPF) di perbankan syariah selama satu dekade terakhir. Penelitian ini difokuskan pada Bank Jatim Syariah karena wilayah layanannya yang luas, basis nasabah yang besar, dan portofolio pembiayaan yang substansial. Dengan menggunakan metode kualitatif, data dikumpulkan melalui wawancara dengan komite pembiayaan dan manajemen bank, serta analisis dokumen pembiayaan pra-pandemi. Temuan penelitian mengungkapkan bahwa Bank Jatim Syariah telah berhasil menerapkan mekanisme mitigasi NPF yang kuat, meliputi restrukturisasi utang, penjadwalan ulang utang, serta strategi penyelesaian sengketa, baik secara litigasi maupun non-litigasi. Langkah-langkah ini secara efektif telah mengurangi tingkat NPF di bawah 2,35%, meminimalkan kerugian bank, dan memastikan kemampuan bank untuk terus melayani 40 juta nasabahnya di Jawa Timur. Studi ini menekankan pentingnya strategi manajemen risiko proaktif dalam menjaga stabilitas dan pertumbuhan lembaga perbankan syariah.